1998
DOI: 10.1007/s004210050360
|View full text |Cite
|
Sign up to set email alerts
|

Plasma volume in acute hypoxia: comparison of a carbon monoxide rebreathing method and dye dilution with Evans' blue

Abstract: Exposure to acute hypoxia is associated with changes in body fluid homeostasis and plasma volume (PV). This study compared a dye dilution technique using Evans' blue (PV[Evans']) with a carbon monoxide (CO) rebreathing method (PV[CO]) for measurements of PV in ten normal subjects at sea level and again 24 h after rapid passive ascent to high altitude (4,350 m). Hypobaric hypoxia decreased arterial oxygen saturation to 79 (74-83)% (mean with 95% confidence intervals). The PV(Evans') remained unchanged from 3.49… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 22 publications
2
20
0
Order By: Relevance
“…The extent to which this occurs remains equivocal, since careful scrutiny of their data reveals that the results may have been unrealistically in¯uenced by one subject who exhibited a 30% decrease in plasma volume as measured by CO-rebreathing (Poulsen et al 1998). However, there is persuasive evidence to suggest that Evans blue dye measurement is not an appropriate technique with which to measure changes in red cell mass consequent to hypoxic exposure.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The extent to which this occurs remains equivocal, since careful scrutiny of their data reveals that the results may have been unrealistically in¯uenced by one subject who exhibited a 30% decrease in plasma volume as measured by CO-rebreathing (Poulsen et al 1998). However, there is persuasive evidence to suggest that Evans blue dye measurement is not an appropriate technique with which to measure changes in red cell mass consequent to hypoxic exposure.…”
Section: Discussionmentioning
confidence: 80%
“…Although there have been studies in which no increase in capillary permeability to albumin was found following altitude exposure (Siggard-Andersen et al 1968;Kleger et al 1996), Poulsen et al (1998) have recently substantiated that Evans blue dye measurement overestimates plasma volume as a consequence of acute altitude exposure when compared to the CO-rebreathing technique. The extent to which this occurs remains equivocal, since careful scrutiny of their data reveals that the results may have been unrealistically in¯uenced by one subject who exhibited a 30% decrease in plasma volume as measured by CO-rebreathing (Poulsen et al 1998).…”
Section: Discussionmentioning
confidence: 94%
“…This is a safe, repeatable method that correlates well with radio-labeled Albumin and Evan's Blue (Poulsen et al 1998;Thomsen et al 1991). This test occurred at 0800 both pre-and post-bed rest.…”
Section: Plasma Volumementioning
confidence: 81%
“…Red blood cell volume, blood volume and plasma volume were determined by a carbon monoxide rebreathing method (Circulating Blood Volume System, CBVMedical, Denmark) (Christensen et al 1993;Poulsen et al 1998). Briefly, after a 20-min resting period in a sitting position, the subjects breathed into a closed circuit, including a 2-l rebreathing bag, and a carbon dioxide absorber.…”
Section: Intra-vascular Compartmentsmentioning
confidence: 99%